2011
DOI: 10.1039/c1em10053j
|View full text |Cite
|
Sign up to set email alerts
|

Climate change drives warming in the Hudson River Estuary, New York (USA)

Abstract: Estuaries may be subject to warming due to global climate change but few studies have considered the drivers or seasonality of warming empirically. We analyzed temperature trends and rates of temperature change over time for the Hudson River estuary using long-term data, mainly from daily measures taken at the Poughkeepsie Water Treatment Facility. This temperature record is among the longest in the world for a river or estuary. The Hudson River has warmed 0.945 °C since 1946. Many of the warmest years in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…The monthly temperature increases are significant (p < 0.05) for the majority of months except for two months in the Phytoplankton Survey temperature data (November, December), four months in Fish Survey temperature data (June, October, November, and December), and three months in the NOAA temperature data (June, July, November). Others have also observed seasonal differences in warming in the Chesapeake Bay (Preston 2004, Najjar et al, 2010 and Hudson River Estuary (Seekell and Pace, 2011). The seasonality associated with warming coastal waters makes it difficult to capture the level of associated ecosystem impact with a single annual value for temperature increase.…”
Section: Narragansett Bay Surface Water Temperature Trendsmentioning
confidence: 96%
“…The monthly temperature increases are significant (p < 0.05) for the majority of months except for two months in the Phytoplankton Survey temperature data (November, December), four months in Fish Survey temperature data (June, October, November, and December), and three months in the NOAA temperature data (June, July, November). Others have also observed seasonal differences in warming in the Chesapeake Bay (Preston 2004, Najjar et al, 2010 and Hudson River Estuary (Seekell and Pace, 2011). The seasonality associated with warming coastal waters makes it difficult to capture the level of associated ecosystem impact with a single annual value for temperature increase.…”
Section: Narragansett Bay Surface Water Temperature Trendsmentioning
confidence: 96%
“…Temperature increases in the northeastern United States have been associated with increased spring water temperatures (McCormick and Fahnenstiel 1999;Nixon et al 2004;Austin and Colman 2008;(Kaushal et al 2010); Seekell and Pace 2011), early iceout (Hodgkins et al 2009), shorter winters with decreased amounts of ice (Assel and Robertson 1995;Assel et al 2003), warmer summers Colman 2007, 2008), and an increase in the frequency of extreme precipitation events (Kunkel et al 2013). Seekell and Pace (2011) and Strayer et al (2014) documented an increasing trend in mean annual water temperature in the Hudson since 1940 or earlier.…”
mentioning
confidence: 99%
“…Higher water temperature can impair the habitat of a wide range of aquatic organisms from invertebrates to salmonids (Langan et al, 2001;Caissie, 2006;Isaak et al, 2012;Markovic et al, 2013;Null et al, 2013a,b), as well as degrade water quality such as decreased oxygen-holding capacity, increased oxygen consumption, and enhanced formation of potentially toxic NH 3 (Webb and Nobilis, 2007;Pekárová et al, 2011;El-Jabi et al, 2014). Furthermore, increasing riverine heat flux has a great potential to aggravate eutrophication (including harmful algal blooms) and hypoxia in downstream lakes, estuaries and coastal waters (Liu et al, 2005;Ozaki et al, 2008;Ye et al, 2011;Rice and Jastram, 2015), as well as to impair their biological communities (Seekell and Pace, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Seekell and Pace (2011) indicated that a 0.945°C increase of water temperature in the Hudson River during the period 1946-2008 was primarily related to air temperature increasing. Depending on the river type and time scale, the air-water temperature dynamics can be effectively http://dx.doi.org/10.1016/j.jhydrol.2015.12.005 0022-1694/Ó 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%